Existential interventions in eating disorders - Thomas, Michael (2001)
This study provides the result of a doctorate research into the impact of existential psychotherapeutic interventions with people experiencing chronic eating disorders. The results indicate that positive outcomes are correlated to therapeutic interventions which concentrate on the clients own perception of control and choice over their own eating habits.